The effect of the circular sports training method when practicing volleyball On volleyball cognitive achievement and knowledge economy - Shaker Mahmood, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
Volleyball is one of the most popular and distinctive international sports that teach us patience, and it benefits health well because it is considered exercise for the body, improves mood, helps to get rid of joint pain, protects against osteoporosis, and helps to improve anxiety, mood, tension, depression, and thinking. Increases muscle strengthening, especially in legs and legs. It creates a spirit of cooperation, interaction, and enthusiasm among individuals, which drives enthusiasm to gain victory and goals. It also helps to get rid of emptiness and boredom in addition to removing fat, calories, and excess weight. Volleyball represents one of the types of team sport that was dealt with by technical and planning development and progress in order to advance it in terms of performance, plans, and methods of play in keeping with the rapid progress in the sports field, especially when compared to the sport at high levels, where the game of volleyball is characterized by the abundance and diversity of its basic motor skills, which is one of the important aspects on which the planning aspects of the game are built. Volleyball is characterized by a rapid transition from defense to attack and vice versa, as it is characterized by continuous interaction between attack and defense throughout the match. The game of volleyball has achieved a widespread use as a result of raising the skill level of the players, and this progress came as a result of the efforts of scientists, researchers and scholars in the academic and applied field, using different training models, the most important of which was the use of circular training that works to improve the skill abilities of the players, as well as the amendments made The volleyball game, which was characterized by rapid accuracy, performance and the use of coaches, various training methods, including the circular method to reach mathematical achievement, as the student now represents the axis on which the learning process revolves and not just a future of information that is dictated to him by the teacher, and through the experience of the researcher as a teacher A practitioner of this game, he noticed that there is a clear weakness among volleyball players, especially in (Achievement) and (Knowledge Economy), and he also noticed that these lessons are presented to all students in the same way and at the same time in a manner that is often specific and repeated, without taking into account individual differences. Between students and their tendencies, attitudes, and desires, and this is due to the low nature of the training programs used by some coaches in the sports field. These patterns are the usual (traditional) training pattern, as well as the culture of coaches sometimes, which he acquired through non-systematic means and methods. The circular training method leads to the development of the skills and qualities of the players.